2008
DOI: 10.28945/1000
|View full text |Cite
|
Sign up to set email alerts
|

Teaching in Virtual Worlds: Opportunities and Challenges

Abstract: How, where, when, and what we teach has been significantly influenced by technological innovation. Radio, television, and computers have all altered how information is presented and how students interact with that information. This paper describes how virtual worlds provide a mechanism to incorporate constructivist, experiential, and student-centered learning practices into the classroom. The authors also discuss the challenges and the benefits of using virtual worlds in education as well as some implications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(48 citation statements)
references
References 0 publications
0
43
0
5
Order By: Relevance
“…In addition, the time needed for designing a virtual environment is disproportionately larger compared to other types of computer applications (Fokides & Zampouli, 2016). Under certain circumstances, for example, courses that have very specific learning objectives, the effort involved is probably unjustifiable (Kluge & Riley, 2008). The above suggest that there are implications for software engineers and designers.…”
Section: Implications For Practicementioning
confidence: 99%
“…In addition, the time needed for designing a virtual environment is disproportionately larger compared to other types of computer applications (Fokides & Zampouli, 2016). Under certain circumstances, for example, courses that have very specific learning objectives, the effort involved is probably unjustifiable (Kluge & Riley, 2008). The above suggest that there are implications for software engineers and designers.…”
Section: Implications For Practicementioning
confidence: 99%
“…Highperceived risk results in risk aversion (e.g., no internet use) and conveying negative information about the technology. Studies have shown that teachers tend to avoid technology use when there is a high-perceived risk (Howard, 2013;Kluge & Riley, 2008). Therefore, this scale can be beneficial for studies investigating teachers' acceptance of technology regarding the internet and technology integration studies.…”
Section: Discussionmentioning
confidence: 99%
“…Penfold (2009) perceives intellectual property and security issues as another downside as well as the existence of an inappropriate content in the world of Second Life. And finally, cost may be a deterrent for some universities as stated by Kluge and Riley (2008).…”
Section: Adaptation Of the Virtual Worlds In Tourism Educationmentioning
confidence: 99%